BMSC-Derived Exosomal miR-29a Promotes Angiogenesis and Osteogenesis - Lu, Guo-dong; Cheng, Peng; Liu, Ting; Wang, Zhong (Frontiers in Cell and Developmental Biology, 2020)
Angiogenesis and osteogenesis are tightly coupled during bone modeling and remodeling processes. Here we reported that bone marrow mesenchymal stem cells (BMSCs) derived exosomal miR-29a promote angiogenesis and osteogenesis in vitro and in vivo. BMSCs-Exos can be taken up by human umbilical vein endothelial cells (HUVECs) and promote proliferation, migration and tube formation of HUVECs. MiRNA-29a level was high in BMSCs-Exos and can be transported into HUVECs to regulate angiogenesis. VASH1 was identified as a direct target of miR-29a mediating the effects of BMSCs derived exosomal miR-29a on angiogenesis. More interestingly, miR29a-loaded exosomes from engineered BMSCs (miR-29a-loaded BMSCs-Exos) showed robust ability of promoting angiogenesis and osteogenesis in vivo. Taken together, these findings suggest that BMSCs derived exosomal miR-29a regulate angiogenesis and osteogenesis and miR-29a-loaded BMSCs-Exos may serve as a potential therapeutic target for osteoporosis.